Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! To match the equations in general form with their corresponding equations in standard form, follow these steps:
1. General Form: [tex]\(x^2 + y^2 - 4x + 12y - 20 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x-6)^2 + (y-4)^2 = 56\)[/tex]
2. General Form: [tex]\(x^2 + y^2 + 6x - 8y - 10 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x-2)^2 + (y+6)^2 = 60\)[/tex]
3. General Form: [tex]\(3x^2 + 3y^2 + 12x + 18y - 15 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x+2)^2 + (y+3)^2 = 18\)[/tex]
4. General Form: [tex]\(5x^2 + 5y^2 - 10x + 20y - 30 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x+1)^2 + (y-6)^2 = 46\)[/tex]
The correct pairs are as follows:
[tex]\[ \begin{array}{l|l} x^2 + y^2 - 4x + 12y - 20 = 0 & (x-6)^2 + (y-4)^2 = 56 \\ x^2 + y^2 + 6x - 8y - 10 = 0 & (x-2)^2 + (y+6)^2 = 60 \\ 3x^2 + 3y^2 + 12x + 18y - 15 = 0 & (x+2)^2 + (y+3)^2 = 18 \\ 5x^2 + 5y^2 - 10x + 20y - 30 = 0 & (x+1)^2 + (y-6)^2 = 46 \\ \end{array} \][/tex]
Remember, the equation [tex]\(2x^2 + 2y^2 - 24x - 16y - 8 = 0\)[/tex] did not match with any of the provided standard form equations.
1. General Form: [tex]\(x^2 + y^2 - 4x + 12y - 20 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x-6)^2 + (y-4)^2 = 56\)[/tex]
2. General Form: [tex]\(x^2 + y^2 + 6x - 8y - 10 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x-2)^2 + (y+6)^2 = 60\)[/tex]
3. General Form: [tex]\(3x^2 + 3y^2 + 12x + 18y - 15 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x+2)^2 + (y+3)^2 = 18\)[/tex]
4. General Form: [tex]\(5x^2 + 5y^2 - 10x + 20y - 30 = 0\)[/tex]
- Corresponding Standard Form: [tex]\((x+1)^2 + (y-6)^2 = 46\)[/tex]
The correct pairs are as follows:
[tex]\[ \begin{array}{l|l} x^2 + y^2 - 4x + 12y - 20 = 0 & (x-6)^2 + (y-4)^2 = 56 \\ x^2 + y^2 + 6x - 8y - 10 = 0 & (x-2)^2 + (y+6)^2 = 60 \\ 3x^2 + 3y^2 + 12x + 18y - 15 = 0 & (x+2)^2 + (y+3)^2 = 18 \\ 5x^2 + 5y^2 - 10x + 20y - 30 = 0 & (x+1)^2 + (y-6)^2 = 46 \\ \end{array} \][/tex]
Remember, the equation [tex]\(2x^2 + 2y^2 - 24x - 16y - 8 = 0\)[/tex] did not match with any of the provided standard form equations.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.